2009
DOI: 10.1107/s0907444909029710
|View full text |Cite
|
Sign up to set email alerts
|

Structure ofD-alanine-D-alanine ligase fromThermus thermophilusHB8: cumulative conformational change and enzyme–ligand interactions

Abstract: d-Alanine-d-alanine ligase (Ddl) is one of the key enzymes in peptidoglycan biosynthesis and is an important target for drug discovery. The enzyme catalyzes the condensation of two d-Ala molecules using ATP to produce d-Ala-d-Ala, which is the terminal peptide of a peptidoglycan monomer. The structures of five forms of the enzyme from Thermus thermophilus HB8 (TtDdl) were determined: unliganded TtDdl (2.3 Å resolution), TtDdl-adenylyl imidodiphosphate (2.6 Å ), TtDdl-ADP (2.2 Å ), TtDdl-ADP-d-Ala (1.9 Å ) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 30 publications
10
48
0
Order By: Relevance
“…In contrast, Mg 2+ ‐2 shows an asymmetric coordination geometry with the carboxy groups of Glu109 and Glu324, the main‐chain carbonyl group of Leu182, and a water molecule. The binding mode of the enzyme with the phosphate groups of ADP, the two magnesium ions, and the phosphate group of the P‐analog is quite similar with those of Ddls and VanA as previously reported 14, 21, 22, 26…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…In contrast, Mg 2+ ‐2 shows an asymmetric coordination geometry with the carboxy groups of Glu109 and Glu324, the main‐chain carbonyl group of Leu182, and a water molecule. The binding mode of the enzyme with the phosphate groups of ADP, the two magnesium ions, and the phosphate group of the P‐analog is quite similar with those of Ddls and VanA as previously reported 14, 21, 22, 26…”
Section: Resultssupporting
confidence: 82%
“…As in the case of DdlB‐related enzymes, the N‐terminal amino acid ( L ‐alanine) first binds to the ATP‐bound state of the enzyme. The previous structural study of Ddl from Thermus thermophilus HB8 in various substrate bound states (PDB IDs: 2YZG, 2YZN, 2ZDG, 2ZDH, and 2ZDQ) has suggested that the binding of the first D ‐alanine should be preceded by the binding of ATP because the loops forming the active site cannot take the conformation suitable for the amino‐acid binding without the ATP binding 26. The bound L ‐alanine is oriented for the phosphate transfer reaction with the aid of Glu273, His301, Glu311, and Gly331, and the carboxy oxygen atom nucleophilically attacks the phosphorous atom in the γ phosphate group [Figs.…”
Section: Resultsmentioning
confidence: 99%
“…This difference could explain the lower affinity for ATP of VRSA-9 Ddl. In a recent work (17), the crystal structure of the Ddl from Thermus thermophilus HB8 identified four conformational states (open, semiopen, semiclosed, and closed), and the reaction catalyzed by the Ddl is considered to proceed through these states. Upon binding of the substrate, the central domain rotates as a rigid body toward the C-terminal domain.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the study of these enzymes is of prime interest in the search for new antimicrobials, particularly by rational drug-design methods. In order to elucidate the structural and chemical basis of enzyme activity, the crystal structures of Ddl from Escherichia coli (Fan et al, 1994), Staphylococcus aureus (Liu et al, 2006), Thermus caldophilus (Lee et al, 2006), Helicobacter pylori (Wu et al, 2008) and T. thermophilus HB8 (Kitamura et al, 2009) have been reported. Additionally, the crystal structures of d-alanyld-lactate ligases from Enterococcus faecium (Roper et al, 2000) and Leuconostoc mesenteroides (Kuzin et al, 2000) have been reported.…”
Section: Introductionmentioning
confidence: 99%